Story Telling Techniques in Group Guidance Services to Increase the Self-Confidence of Thai Postage School Students - Qurratul Aini; Sri Ngayomi Yudha Wastuti; M Fauzi Hasibuan (Universitas Muhammadiyah Enrekang, 2024)
Study This study uses a case study approach to explore the application of storytelling techniques in group guidance services to increase the self-confidence of class X students at Thammasat Wittaya Satun School, Thailand. Literature analysis and initial observations show students' low self-confidence, especially in public speaking. This research involves the application of storytelling techniques in group guidance services, by monitoring student reactions and collecting qualitative data through interviews. The results show an increase in students' self-confidence after active participation in storytelling activities.